Multi-modal magnetic resonance imaging in a mouse model of concussion - Xuan Vinh To; Fatima A. Nasrallah (Scientific Data, 2021)
Measurement(s) brain measurement Technology Type(s) magnetic resonance imaging (MRI) Sample Characteristic - Organism Mus musculus Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14813325